Risk Factors for Radiation-Induced Keratoconjunctivitis Sicca in Dogs Treated with Hypofractionated Intensity-Modulated Radiation Therapy for Intranasal Tumors - Akihiro Ohnishi; Soichirou Takeda; Yoshiki Okada; Manami Tokoro; Saki Kageyama; Yoshiki Itoh; Taketoshi Asanuma (Animals)
Radiation-induced keratoconjunctivitis sicca (KCS) is a significant late complication in dogs receiving radiation therapy for intranasal tumors, particularly with hypofractionated intensity-modulated radiation therapy (IMRT). This retrospective case-control study was performed to identify anatomical and dosimetric risk factors for KCS in 15 canine patients treated with IMRT delivered in 4–6 weekly fractions of 8 Gy. Orbital structures were retrospectively contoured, and dose–volume metrics (D50) were calculated. Receiver operating characteristic (ROC) curve analysis and odds ratios were used to evaluate the associations between radiation dose and KCS development. Six dogs (33%) developed KCS within three months post-treatment. Statistically significant dose differences were observed between affected and unaffected eyes for the eyeball, cornea, and retina. ROC analyses identified dose thresholds predictive of KCS: 13.8 Gy (eyeball), 14.9 Gy (cornea), and 17.0 Gy (retina), with the retina showing the highest odds ratio (28.33). To ensure clinical relevance, KCS was diagnosed based on decreased tear production combined with corneal damage to ensure clinical relevance. This study proposes dose thresholds for ocular structures that may guide treatment planning and reduce the risk of KCS in canine patients undergoing IMRT. Further prospective studies are warranted to validate these thresholds and explore mitigation strategies for high-risk cases.